Global electric circuit parameters and their variability observed over Maitri, Antarctica - Jeeva, K.; Panneerselvam, C.; Nair, K.U.; Selvaraj, C.; Dhar, Ajay; Pathan, B.M.; Gurubaran, S. (2011)
The global component of fairweather electricity is subject to special attention to watch the solar-terrestrial effects and secular changes in climate. It is generally considered that the diurnal variation of atmospheric electricity parameters, if they are not following the Carnegie pattern, are not representative of the global thunderstorm activity. Some of the results obtained from Maitri (70°45′54″S, 11°44′03″), are discussed here in context with global thunderstorm activity and space weather influences. The diurnal pattern of the Potential Gradient and current density strongly deviate from the Carnegie curve. We have showed that this deviation is not due to the local electrical influence but due to the global thunderstorm activity. During fairweather condition the parameters are representing the global thunderstorm activity and to some extent they respond to the upper atmospheric electro dynamic phenomenon. The mean value of the potential gradient (77.7 V/m) and current density (2.13 pA/m2) well below the expected global mean but close to the value reported from the same location and season in the past years. The mean conductivity, 3.34 × 10−14 mhom−1, is slightly at higher side and they exhibit a different diurnal trend comparing to the past measurements at this location.